A Temática Ambiental e a Educação Profissional: Uma Articulação Necessária na Formação do Técnico Agrícola - Carvalho, João Flávio Cogo (2004)
This work is linked to the research group in scientific, technologic and mathematics education and to the research line education practices in institutions of the post-graduation program in education of Federal University of Santa Maria. This research aims at study conceptions and practices in relation to environmental education that compose professional education of agricultural Technician in Federal Center of Technological Education (CEFETSVS/RS). Such approach brings to educational setting questions about the kind of activities that technicians are able to perform in rural and urban companies linked to the rural activities, as the orientation of rural producers about agricultural production that can respect the environment and the producer and consumer s life. These activities is linked to technician s important leadership in the search of environmental protection. The main objective is to study the insertion forms of environmental education in the agricultural technician course, the practices and conceptions of environmental education studied, according to documental analyses of curricular parameters of professional education agricultural area, the subject programs that compose the technician course and questionnaires sent to teachers and students and the observation of some classes. A first find shows that curricular parameters of professional education and the programs of the subjects have a group of suggested competence in the curriculum associated to environmental education. On the other hand, there are subjects related more directly to environmental education, due to they deal with natural resources, however the approach used in these subjects is linked to biologic and economic aspects. The social, politic and ethic aspects of environment are rarely discussed. Teachers and students describe their worry with environmental questions and they have pointed as great problems the management pests and diseases in agricultural growing, animal creation and destine of food production residue. To sum up it is necessary that school promotes an interdisciplinary work in order to give a wider and deeper view in relation to environmental education and to offer the students a better technical formation based in human and environmental conscientiousness, as the present world demands.